Gagea kotuchovii (Liliaceae) a new species from the Karatau Mountains (western Tian Shan, Kazakhstan) evidenced by morphological and molecular analyses - Serik Kubentayev; Igor Levichev; Shukherdorj Baasanmunkh; Ewelina Klichowska; Daniyar Alibekov; Hyeok Jae Choi; Marcin Nobis (PLoS ONE, 2025)
Gagea kotuchovii (Liliaceae) a new narrow endemic species growing exclusively in the Karatau Mountains in South Kazakhstan, is here described and illustrated. It is a unique species within the section Gagea , differing from closely related taxa by the presence of several stolons of different lengths (0.5–8 cm), formed on a single vegetative individual, as well as a unique bulb with a densely woolly sheath. Morphological characteristics, distribution map, and illustrations of the habit and habitats of the new species are presented. We also present phylogenetic analyses based on the internal transcribed spacer (ITS) of nuclear DNA and SNPs obtained from DArT genome-wide sequencing (Diversity Arrays Technology sequencing), which confirmed the isolated position of G. kotuchovii but also revealed its phylogenetic relation with morphologically similar species. Additionally, our results reveal phylogenetic intergeneric organization of Gagea representatives occurring in Kazakhstan and/or Middle Asia. To facilitate morphological identification of Asian Gagea with stolons, and similar to G. kotuchovii , we present an identification key.